2016
DOI: 10.5603/imh.2016.0027
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma in maritime environments: an update

Abstract: (Int Marit Health 2016; 67, 3: 144-152)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Parvalbumin is the most common allergen in salmon allergic reaction. However, sensitisation to other protein as tropomyosin, preservatives as sodium metabisulphite, formaldehyde and spices could occur [2,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parvalbumin is the most common allergen in salmon allergic reaction. However, sensitisation to other protein as tropomyosin, preservatives as sodium metabisulphite, formaldehyde and spices could occur [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Various seafood and fishes are known to cause occupational asthma (OA), contact urticaria (CU) and protein contact dermatitis. In the majority of published clinical cases, allergic occupational diseases are separately diagnosed [1,2]. We report a case of occupational allergy to salmon combining allergic asthma, allergic rhinitis and allergic CU.…”
Section: Introductionmentioning
confidence: 96%
“…Research has identified sodium disulfite, used to store fish and seafood, exposure as a cause of asthma. Allergic reactions can also result from exposure to antifouling paints containing fungicides such as chlorothalonil; cleaning products that contain ammonium compounds, chloramine, and Chloramine-T; and diesel engine exhaust [27]. Lucas et al described sodium metabisulfite a significant asthma hazards among mariners including fishers [58], which Durborow also addressed regarding fishers and fish farmers [59].…”
Section: Breathing Hazardsmentioning
confidence: 99%
“…Allergic reactions can also result from exposure to antifouling paints containing fungicides such as chlorothalonil; cleaning products that contain ammonium compounds, chloramine, and Chloramine-T; and diesel engine exhaust [27]. Lucas et al described sodium metabisulfite a significant asthma hazards among mariners including fishers [58], which Durborow also addressed regarding fishers and fish farmers [59]. Sharp and Lopata also found that some physical factors (such as cold air and high physical activity) may trigger respiratory symptoms [33].…”
Section: Breathing Hazardsmentioning
confidence: 99%
“…Often, a latency period of approximately two years exists from occupational exposure until OA develops, which makes it important to diagnose OA early in order to remove the allergen and prevent further aggravation of the disease (15). It has been found that lung function improves within a year after removal from exposure and bronchial reactivity within two years which is followed by a subsequent plateau (20)(21)(22). The short latency period increases the risk of a healthy worker effect in the mainly cross-sectional studies performed earlier since the sick workers are assumed to leave the industries shortly after employment (23).…”
Section: Occupational Asthma and Allergy In The Seafood-processing In...mentioning
confidence: 99%